TEORI BAGI HASIL (PROFIT AND LOSS SHARING) DAN PERBBANKAN SYARIAH DALAM EKONOMI SYARIAH - Yahya, Muchlis; Agunggunanto, Edy Yusuf (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2011)
Profit sharing (Mudharabah) is a monetary instrument of Islamic finance as interest is a monetaryinstrument of conventional economics. Both have extreme one another paradigm. Results have a theoreticalbasis for the profit and loss sharing (PLS). PLS theory was built as a new offer on the outside of the systemwhich tend not to reflect the interest of justice (injustice / dzalim) due to discrimination against the sharingof risks and profits for economic actors. Profit-loss sharing means profits and or losses that may arise fromeconomic activities / business borne together. In the instrument for the results are not fixed and there is a certainreturns as interest, but do profit and loss sharing based on the real productivity of the product. Therefore thesystem to better reflect the outcome of justice. Profit sharing as a monetary instrument has been frequentlyapplied in studies of Islamic economics, both from the supply side (financing) or the supply side economicsand/or demand-side economics.